Safety and Efficacy of Intravenous Ferric Carboxy Maltose in Iron Deficiency Anaemia During Postpartum Period - Mishra, Vineet; Roy, Priyankur; Gandhi, Khushali; Choudhary, Sumesh; Aggarwal, Rohina; Hokabaj, Shaheen (Journal of Nepal Health Research Council, 2018)
Background: Iron deficiency is the commonest treatable cause of postpartum anaemia. Parenteral iron therapy results in faster and higher replenishment of iron stores and correction of haemoglobin levels with better compliance. Ferric Carboxy Maltose is an effective and a safe option which can be administered intravenously in single total correction dose without any serious adverse effects.The study was done to evaluate the efficacy and safety of Ferric Carboxy Maltose in the treatment of iron deficiency anaemia in post-natal patients. Methods: It was an open, single arm study including 615 women with diagnosis of Iron deficiency anaemia and haemoglobin (Hb) levels between 4gm% and 11gm% from January 2013 to December 2016. Intravenous Ferric Carboxy Maltose(500-1500mg) was administered and the improvement in haemoglobin levels and iron stores were assessed after three weeks of total dose infusion. Results: Out of the 615 women, 595 women were included in the analysis. Most of the women were in the age group of 27-30 years. Most of the women had mild anaemia as per World Health Organisation guidelines. Mean hemoglobin levels significantly increased over a period of three weeks after Ferric Carboxy Maltose administration. Other parameters like total iron binding capacity, Ferritin and Iron also had a significant improvement after Ferric Carboxy Maltose administration. No serious adverse events were observed after Ferric Carboxy Maltose. Conclusions: Intravenous Ferric Carboxy Maltose was an effective and a safe treatment option for iron deficiency anaemia and has an advantage of single administration of high doses without serious adverse effects.